Pseudomonas aeruginosa and Klebsiella pneumoniae Adaptation to Innate Immune Clearance Mechanisms in the Lung - Sebastián Riquelme-Barrios; Danielle Ahn; Alice Prince (2018)
Many different species of gram-negative bacteria are associated with infection in the lung, causing exacerbations of chronic obstructive pulmonary disease, cystic fibrosis (CF), and ventilator-associated pneumonias. These airway pathogens must adapt to common host clearance mechanisms that include killing by antimicrobial peptides, antibiotics, oxidative stress, and phagocytosis by leukocytes. Bacterial adaptation to the host is often evident phenotypically, with increased extracellular polysaccharide production characteristic of some biofilm-associated organisms. Given the relatively limited repertoire of bacterial strategies to elude airway defenses, it seems likely that organisms sharing the same ecological niche might also share common strategies to persistently infect the lung. In this review, we will highlight some of the major factors responsible for the adaptation of Pseudomonas aeruginosa to the lung, addressing how growth in biofilms enables persistent infection, relevant to, but not limited to, the pathogenesis of infection in CF. In contrast, we will discuss how carbapenem-resistant Klebsiella pneumoniae evade immune clearance, an organism often associated with ventilator-associated pneumonia and health-care-acquired pneumonias, but not a typical pathogen in CF.